2019
DOI: 10.3892/mmr.2019.10085
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑494 inhibits apoptosis of murine vascular smooth muscle cells in�vitro

Abstract: Apoptosis of vascular smooth muscle cells (VSMCs) is a process that regulates vessel remodeling in various cardiovascular diseases. The specific mechanisms that control VSMC apoptosis remain unclear. The present study aimed to investigate whether microRNA-494 (miR-494) is involved in regulating VSMC apoptosis and its underlying mechanisms. Cell death ELISA and terminal deoxynucleotidyl-transferase-mediated dUTP nick end labeling assays were used to detect apoptosis of murine VSMCs following stimulation with tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Neural stem cells differentiated from ESCs are suggested to be involved in cognition impairment-related diseases in humans (41,42). miR-467a-3p has also previously been found to be involved in the apoptosis of vascular smooth muscle cells (43). The present study showed that miR-467a-3p was differentially expressed in the hippocampus tissues of mice exposed to sevoflurane, which indicated that the neural differentiation and proliferation were dysregulated upon sevoflurane exposure.…”
Section: Discussionsupporting
confidence: 64%
“…Neural stem cells differentiated from ESCs are suggested to be involved in cognition impairment-related diseases in humans (41,42). miR-467a-3p has also previously been found to be involved in the apoptosis of vascular smooth muscle cells (43). The present study showed that miR-467a-3p was differentially expressed in the hippocampus tissues of mice exposed to sevoflurane, which indicated that the neural differentiation and proliferation were dysregulated upon sevoflurane exposure.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, hypoxia exposure induces significant increases in In addition to growth factors, miRNAs also exert a key effect on angiogenesis via modulating the proliferation, differentiation, apoptosis, migration, and vascularization of angiogenesis-associated cells that play an essential role in numerous physiological and pathological processes (Sun, Li, Lei, & Li, 2018). miRNAs affect the regulation of post-transcriptional genes via binding to mRNAs in their 3′-UTRs, thus inducing translation degradation or obstruction within various biological processes (Cui et al, 2019;Karreth et al, 2011;Liu et al, 2019;Lu et al, 2018;Lucas et al, 2017;Siomi & Siomi, 2010;Thamotharan et al, 2017 -17-5p, miR-17-3p, miR-18a, miR-19a, miR-20a, miR-19b, and miR-92a, demonstrate a variety of biological effects on angiogenesis (Dews et al, 2006;Landskroner-Eiger et al, 2015). miR-92a and miR-20a can target vascular endothelial growth factor A (VEGFA) and integrin subunit alpha 5 to suppress angiogenesis (Landskroner-Eiger et al, 2015).…”
Section: Discussionmentioning
confidence: 64%
“…In addition to growth factors, miRNAs also exert a key effect on angiogenesis via modulating the proliferation, differentiation, apoptosis, migration, and vascularization of angiogenesis‐associated cells that play an essential role in numerous physiological and pathological processes (Sun, Li, Lei, & Li, ). miRNAs affect the regulation of post‐transcriptional genes via binding to mRNAs in their 3′‐UTRs, thus inducing translation degradation or obstruction within various biological processes (Cui et al, ; Karreth et al, ; Liu et al, ; Lu et al, ; Lucas et al, ; Siomi & Siomi, ; Thamotharan et al, ). Interestingly, several miRNAs have been reported to exert a dual function on angiogenesis, depending on the cell type and their downstream targets.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies demonstrated that miRNA-494 mediated human nucleus pulposus and liver cell apoptosis [34,35], by the contrast, other studies found that it had an opposite effect on cardiomyocyte and vascular smooth muscle cell apoptosis [36,37]. The effect of miRNA-494-3p on apoptosis was similar with that of miRNA-494 [38][39][40].…”
Section: Discussionmentioning
confidence: 96%